2010
DOI: 10.1182/blood-2009-10-249847
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-type MMPs are indispensable for placental labyrinth formation and development

Abstract: IntroductionAfter embryo implantation and decidualization, a critical step in placental development is the formation of the placental labyrinth (LA), which enables nutrient and gas exchange between the embryonic vasculature and the maternal blood supply. 1-5 LA formation is associated with substantial tissue remodeling and cell differentiation, as well as ingrowth of the embryonic vasculature through the chorion to a point of immediate proximity with the maternal blood supply. During this process, chorionic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…Results such as ours are often countered by the argument that the mouse genome encodes more than 20 MMP family members, but virtually all of these genes have now been targeted and, with the exception of Mmp14, each knockout gives rise to viable mice with normal lifespans (Bonnans et al, 2014;Holmbeck et al, 1999;Itoh, 2015;Rowe and Weiss, 2009;Zhou et al, 2000). The fact that only Mmp14 targeting causes a dramatic increase in the morbidity and mortality of knockout mice (Holmbeck et al, 1999;Zhou et al, 2000) and that dual targeting of Mmp14 and Mmp15 results in an embryonic lethal phenotype (Szabova et al, 2010) have, predictably, catalyzed increased efforts to identify the key functions of these proteinases. Clearly, MMP14 and MMP15 do exert complex effects on mammary gland development, but the observed changes in function are, for the most part, novel and unanticipated from the perspective of current paradigms.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Results such as ours are often countered by the argument that the mouse genome encodes more than 20 MMP family members, but virtually all of these genes have now been targeted and, with the exception of Mmp14, each knockout gives rise to viable mice with normal lifespans (Bonnans et al, 2014;Holmbeck et al, 1999;Itoh, 2015;Rowe and Weiss, 2009;Zhou et al, 2000). The fact that only Mmp14 targeting causes a dramatic increase in the morbidity and mortality of knockout mice (Holmbeck et al, 1999;Zhou et al, 2000) and that dual targeting of Mmp14 and Mmp15 results in an embryonic lethal phenotype (Szabova et al, 2010) have, predictably, catalyzed increased efforts to identify the key functions of these proteinases. Clearly, MMP14 and MMP15 do exert complex effects on mammary gland development, but the observed changes in function are, for the most part, novel and unanticipated from the perspective of current paradigms.…”
Section: Discussionmentioning
confidence: 80%
“…As Mmp14/Mmp15 double-null mice die during embryogenesis (Szabova et al, 2010), we alternatively targeted both proteinases selectively in the mammary epithelial compartment, but these analyses demonstrated that branching morphogenesis nevertheless proceeds in a normal fashion from birth through adulthood (our unpublished observations). Interestingly, a double-knockout system was recently employed to target Mmp14 and Mmp15 in postnatal mice wherein mammary gland involution was unaffected (Szabova et al, 2010), suggesting that adult mammary tissue remodeling likewise proceeds in a MT-MMP-independent fashion. Although MMP14 and MMP15 have previously been shown to endow neoplastic cells with the ability to degrade basement membrane (BM) barriers (Ota et al, 2009), it should be stressed that there is no evidence that mammary epithelial cells dissolve their underlying BM during morphogenesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As shown previously, MT1-MMP and MMP2 were present in fetal trophoblast cells of human placenta used as positive control (data not shown; ref. 48). …”
Section: Resultsmentioning
confidence: 99%
“…The fetal portion of the placenta, in particular the labyrinth (LA), displays strong overlapping expression of MT1-MMP and MT2-MMP, which is critical for syncytiotrophoblast formation and for fetal vessels. Both MT1-MMP and MT2-MMP are crucial specifically during development of LA, showing a selective temporal and spatial MMP activity required for the development of the mouse embryo (Szabova et al, 2010). The trophoblast compartment of the placenta comprises various subpopulations with distinct functions.…”
Section: Biological Featuresmentioning
confidence: 99%